Effective isopropanol–butanol (IB) fermentation with high butanol content using a newly isolated Clostridium sp. A1424. Issue 1 (December 2016) - Youn, Sung; Lee, Kyung; Kim, Ki-Yeon; Lee, Sun-Mi; Woo, Han; Um, Youngsoon
Abstract Background Acetone–butanol–ethanol fermentation has been studied for butanol production. Alternatively, to achieve acetone-free butanol production, use of clostridium strains producing butanol and 1, 3-propanediol (1, 3-PDO) from glycerol, natural and engineered isopropanol–butanol–ethanol (IBE) producers has been attempted; however, residual 1, 3-PDO and acetone, low IBE production by natural IBE producers, and complicated gene modification are limitations. Results Here, we report an effective isopropanol and butanol (IB) fermentation using a newly isolatedClostridium sp. A1424 capable of producing IB from various substrates with a small residual acetone. Notably, this strain also utilized glycerol and produced butanol and 1, 3-PDO. After 46.35 g/L of glucose consumption at pH 5.5-controlled batch fermentation, Clostridium sp. A1424 produced 9.43 g/L of butanol and 13.92 g/L of IB at the productivity of 0.29 and 0.44 g/L/h, respectively, which are the highest values in glucose-based batch fermentations using natural IB producers. More interestingly, using glucose–glycerol mixtures at ratios ranging from 20:2 to 14:8 led to not only acetone-free and 1, 3-PDO-free IB fermentation but also enhanced IB production along with a much higher butanol content (butanol/isopropanol ratio of 1.81 with glucose vs. 2.07–6.14 with glucose–glycerol mixture). Furthermore, when the mixture of glucose and crude glycerol at the ratio of 14:8 (total concentration of 35.68 g/L) was used, high butanol/isopropanol ratio (3.44) and butanol titer (9.86 g/L) were achieved with 1.4-fold enhanced butanol yield (0.28 g/g) and productivity (0.41 g/L/h) compared to those with glucose only at pH 5.5. Conclusions A newly isolatedClostridium sp. A1424 was able to produce butanol and isopropanol from various carbon sources. The productivity and titer of butanol and total alcohol obtained in this study were higher than the previously reported results obtained using other natural IB producers. Use of the mixture of glucose and glycerol was successful to achieve acetone-free, 1, 3-PDO-free, and enhanced IB production with higher yield, productivity, and selectivity of butanol compared to those with glucose only, providing great advantages from the perspective of carbon recovery to alcohols. This notable result could be accomplished by isolating an effective IB producerClostridium sp. A1424 as well as by utilizing glucose–glycerol mixtures.